Performance and return to sport after excision of the fractured hook of the hamate in professional baseball players - Erickson, B. J.; McElheny, K.; Chalmers, P. N.; Carr, J. B.; D'Angelo, J.; Rowe, D.; Poulis, G.; Lourie, G. M.; Carlson, M. (The American Journal of Sports Medicine, 2020)
Background: A fracture of the hook of the hamate is a common injury affecting professional baseball players. The treatment for these fractures ranges from nonoperative immobilization to excision of the fragment.